The nature and value of knowledge. Issue 6 (5th June 2017) - De Toni, Alberto Felice; Fornasier, Andrea; Nonino, Fabio
Abstract : Purpose: This paper aims to explain and discuss the complex nature and value of knowledge as an exploitable resource for business. Design/methodology/approach: The authors propose a conceptual explanation of knowledge based on three pillars: the plurality of its nature, understood to be conservative, multipliable and generative, its contextual value and the duality of carrier incorporating business knowledge, objects or processes. After conceptualizing the nature of knowledge, the authors offer a metaphor based on the classic transformation from "potential" to "kinetic" energy in an inclined plane assuming that the conservative nature of knowledge makes it act as energy. Findings: The metaphor uses the concept of potential and kinetic energy: if energy is only potential, it has a potential value not yet effective, whereas if the potential energy (knowledge) becomes kinetic energy (products and/or services), it generates business value. In addition, business value is a function of the speed acquired and caused by the angle of inclined plan, namely, the company's business model. Knowledge is the source of the value and can be maintained and regenerated only through continuous investments. Several years later the value extraction reaches a null value of the company (potential energy) which will cease to act (kinetic energy) for triggering both the value generated and the value extracted. Originality/value: The paper proposes an initial attempt to explain the meaning of the transformation of knowledge using a metaphor derived from physics. The metaphor of the energy of knowledge clearly depicts the managerial dilemma of balancing a company's resources for both the generating and extracting value. Similarly, future study should try to associate other knowledge peculiarities to physical phenomena.